Optimising the use of visual and radar observations for the mitigation of wind energy related impacts on Cape Vultures (Gyps coprotheres) in the Eastern Cape Province - Becker, Frowin Klaus (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.